Moral Disengagement, Dark Triad and Face Mask Wearing during the COVID-19 Pandemic - Chávez-Ventura, Gina (2022)
Not wearing a face mask, despite the sanitary recommendation, represented a public health risk during the COVID-19 pandemic. For this reason, the aim of the study was to determine the mediating role of moral disengagement in the relationship between the dark triad and face mask wearing during the second wave of the pandemic. We worked with a sample made up of 534 adults, who were administered the Dirty Dozen Dark test, the Moral Disengagement Mechanisms Scale and a questionnaire on the frequency of use of face masks. The results showed that moral disengagement mediates the effect of each trait of the dark triad (Machiavellianism, psychopathy and narcissism) on the use of face masks. It is concluded that those who possess any of the dark personality traits morally disengage in order not to use a face mask, exercising a reckless behavior of the possible contagion of COVID-19 to others.